A family of memristor‐based reactance‐less oscillators. (11th April 2013) - Zidan, Mohammed Affan; Omran, Hesham; Smith, Casey; Syed, Ahad; Radwan, Ahmed Gomaa; Salama, Khaled Nabil
SUMMARY In this paper, we present for the first time a family of memristor‐based reactance‐less oscillators (MRLOs). The proposed oscillators require no reactive components, that is, inductors or capacitors, rather, the 'resistance storage' property of memristor is exploited to generate the oscillation. Different types of MRLO family are presented, and for each type, closed form expressions are derived for the oscillation condition, oscillation frequency, and range of oscillation. Derived equations are further verified using transient circuit simulations. A comparison between different MRLO types is also discussed. In addition, detailed fabrication steps of a memristor device and experimental results for the first MRLO physical realization are presented. Copyright © 2013 John Wiley & Sons, Ltd.